Optimization of the Synthesis of Natural Polymeric Nanoparticles of Inulin Loaded with Quercetin: Characterization and Cytotoxicity Effect - Jocelyn C. Ayala-Fuentes; Melissa Zulahi Gallegos-Granados; Luis Jesús Villarreal-Gómez; Marilena Antunes-Ricardo; Daniel Grande; Rocio Alejandra Chavez-Santoscoy (MDPI AG, 2022)
Quercetin is a bioactive component that is capable of having therapeutic potential in the prevention of different noncommunicable chronic diseases (NCDs). However, it presents instability in the gastrointestinal tract in addition to low bioavailability. One way to overcome the limitations of quercetin lies in using nanotechnology for the development of nanoparticles, based on biopolymers, that are capable of being ingestible. Inulin, a fructan-type polysaccharide, acts as a delivery system for the release of quercetin in a target cell, guaranteeing the stability of the molecule. Inulin-coated quercetin nanoparticles were synthesized by the spray dryer method, and four variables were evaluated, namely inulin concentration (5-10% w/v), feed temperature (40-60 °C), inlet temperature (100-200 °C) and outlet temperature (60-100 °C). The optimal conditions were obtained at 10% w/v inulin concentration, with 45 °C feed temperature, 120 °C inlet temperature and 60 °C outlet temperature, and the nanoparticle size was 289.75 ± 16.3 nm in water. Fluorescence microscopy indicated quercetin loading in the inulin nanoparticles, with an encapsulation efficiency of approximately 73.33 ± 7.86%. Inulin-coated quercetin nanoparticles presented effects of inhibition in Caco-2 and HepG2 cells, but not in HDFa cells. The experimental data showed the potential of inulin nanoparticles as transport materials for unstable molecules, in oral administration systems, for the encapsulation, protection and release of quercetin.